Total Tract Dry Matter Digestibility and Proportions of Ruminal Propionate Are Increased in High-Energy Limit-Fed Diets Based Primarily on Wet Corn Gluten Feed - T. J. Spore; S. P. Montgomery; E. C. Titgemeyer; G. A. Hanzlicek; Christopher Vahl; T. G. Nagaraja; K. T. Cavalli; W. R. Hollenbeck; R. N. Wahl; Dale Blasi (Kansas Agricultural Experiment Station Research Reports, 2018)
Objectives:Study digestion and characteristics of digestion of high-energy limit-fed diets based primarily on wet corn gluten feed. Study Description:Six ruminally-cannulated Jersey crossbred steers were used to measure total tract diet digestibility, passage rate, volatile fatty acid, and ammonia production, and ruminal pH when limit-feeding high-energy diets based primarily on wet corn gluten feed. The Bottom Line:High-energy limit-fed diets based primarily on wet corn gluten feed are 15% more digestible and produce a higher concentration of energy yielding volatile fatty acid compared to low-energy full-fed diets without apparent disruptions in ruminal fermentation or health.
Keywords: Stocker cattle; limit-feeding; digestibility